Mediating Role of Employee Readiness to Change in the Relationship of Change Leadership with Employees' Affective Commitment to Change - Amir Mahmud (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the effect of Brand Awareness and Brand Image on Trust and Purchase Intention of online shop consumers in South Sulawesi. This research is included in the type of causal research because this study aims to determine the causal relationship between variables, one variable causes or determines the value of another variable. The sample in this study amounted to 150 people with random sampling method. The results obtained by all independent variables have a significant effect on Purchase Intention and Brand Awareness and Brand Image variables have a significant effect on Purchase Intention through Trust.